Two new ent-kaurane diterpenoids from Wedelia trilobata (L.) Hitchc. (March 2015) - Ren, Hui; Xu, Qiao-Lin; Luo, Ying; Zhang, Mei; Zhou, Zhong-Yu; Dong, Li-Mei; Tan, Jian-Wen
Graphical abstract: Highlights: A rare 18-nor- ent -kaurane diterpenoid (1 ) and a new chlorine-containing diterpenoid (2 ) were isolated. Five known ent -kaurane diterpenoids (3 –7 ) were also isolated from W. trilobata . The new structures were elucidated by spectroscopic techniques. Compounds4 –6 showed moderate or significant in vitro antibacterial activity. Abstract: Two new ent -kaurane diterpenoids, 16 α, 17, 19-trihydroxy-18-nor- ent -kauran-4 β -ol (1 ) and 17-chloro-16 β -hydroxy- ent -kauran-19-oic acid (2 ) were isolated from the whole plant of Wedelia trilobata, together with five known ones (3 –7 ). Their structures were elucidated on the basis of extensive spectroscopic analyses, including NMR and MS techniques. Compound1 is an 18-nor- ent -kaurane type diterpenoid which is rare in nature, and compound2 is the first chlorine-containing ent -kaurane diterpenoid so far isolated from plant family of Asteraceae. Known compound4 was obtained from the genus Wedelia for the first time. Compounds4 –6 selectively showed in vitro antibacterial activity against three assayed Gram-(+) bacteria, especially5 and6 which showed the antibacterial activity against Staphylococcus aureus with MIC values (3.125–6.25 μg/mL) comparable to reference compound Kanamycin (MIC 3.125 μg/mL). Compounds4 –6 further displayed significant antibacterial activity against Gram-(−) bacterium Shigella dysenteriae with MIC value 3.125–12.5 μg/mL.